RESEARCH AND CONTROL MEASURES OF POWDERY MILDEW (OIDIUM) DISEASES IN VINE FRUIT PRODUCTION - Zufarzhon Zafarovich Kodirov; Abrolov Anvarjon Ahmadjonovich (European Science Publishing, 2023)
The geographical location and soil-climatic conditions of the republic are very favorable for the development of all types of agriculture. It is estimated that 35% of the world's crop is lost each year, 14% of which is due to pests and diseases, while 20% of the crop is transported and stored dies during. In our country, various pests and diseases can damage agricultural crops. Pests such as apples, spider mites, grape mites, and aphids are particularly harmful, as are dew, rust, and other diseases.
Keywords: Fruit, oidium, diphenoconazole, krezoksim-methyl, penconazole, tebuconazole, propiconazole, ampact, impact, fungicide.